English Tsunami in Indonesian - Sadtono, E. (Widya Mandala Catholic University Surabaya, 2013)
English has successfully overwhelmed Indonesian like tsunami as an imperialistic language. The meaning of imperialism here, however, differs from the conventional meaning as it is invited imperialism, not coerced imperialism.The influence of English in Indonesian is discussed in terms of modernization, globalization, economy, and history. The linguistic tsunami effects are overwhelming, staggering, and unstoppable. The data for this article were collected from various sources, and it was found that the number of English words (pure and modified) is indeed confounding. Virtually English words have penetrated all walks of life. Unfortunately, there is no way we can prevent English influence on Indonesian, it is simply inevitable and we cannot do anything about it. Seen from linguistic purism, we have lost the battle in fighting off English influence; but seen from the eye of a descriptive linguist, it is an unpreventable historical phenomenon. It is a lingusitic dynamism in which language is altered and enriched by a continuous input from other languages, the most influential language being the major donor of loanwords of the receiving language. If it is considered a problem, the solution is to change our attitude to realize that any living language continues undergoing modifications and we should be willing to accommodate them. It is the dialectics of world history.